1999
DOI: 10.1029/1999rs900002
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the protonosphere on GPS observations: Model simulations

Abstract: Abstract. The accuracy of the Global Positioning System (GPS) satellite navigation system can be degraded by propagation effects on ray paths through the ionized atmosphere. The bulk of the plasma resides in the F layer, and models of total electron content have been developed to compensate for the effects of this ionization. However, use of the GPS system involves long ray paths through the tenuous hydrogen-based plasma of the protonosphere, and little is known about the electron content in this region. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
62
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 14 publications
7
62
1
Order By: Relevance
“…This upper limit was In experimental observations using actual GPS satellites, the ray paths encounter electrons not only in the ionospheric F layer but also in the hydrogendominated plasma of the protonosphere between 1100 km and the GPS altitude of 20200 km. A study using the SUPIM model of the potential influence of protonospheric electrons on GPS ray paths has been described by Lunt et al [1999a]. It was concluded that for observations at European midlafmdes at solar minimum, the electrons above l100 km only contributed a few TEC units to the total electron content.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This upper limit was In experimental observations using actual GPS satellites, the ray paths encounter electrons not only in the ionospheric F layer but also in the hydrogendominated plasma of the protonosphere between 1100 km and the GPS altitude of 20200 km. A study using the SUPIM model of the potential influence of protonospheric electrons on GPS ray paths has been described by Lunt et al [1999a]. It was concluded that for observations at European midlafmdes at solar minimum, the electrons above l100 km only contributed a few TEC units to the total electron content.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that while this condition may not always be valid for European observations at solar minimum, there are many circumstances in which the assumption can hold. The modeling studies of Lunt et al [1999a] showed that because of the tilt of the Earth's magnetic field, the fractional contribution to the electron content arising from the protonosphere was much smaller for observations at )unerican longitudes than for …”
Section: Discussionmentioning
confidence: 99%
“…6) as expected from the latitude variation of PEC. Recently, Lunt et al (1999) estimated the plasmaspheric electron content in GPS ray paths at altitudes above 1100 km in the European and American sectors during magnetically quiet periods at low and high solar activities. According to their estimates, the European sector contains up to 4 TEC units of vertical PEC at 40…”
Section: Resultsmentioning
confidence: 99%
“…The difference between the two gives PEC (=TEC−IEC). There has been some arbitrariness in selecting the base altitude of the plasmasphere (Lunt et al, 1999) (Fig. 3(a)) to 780 km at midnight (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation